1979
DOI: 10.1017/s0021859600062900
|View full text |Cite
|
Sign up to set email alerts
|

Drought tolerance in potatoes

Abstract: SummaryIn field experiments made over 3 years Pentland Crown and Majestic gave, in general, higher total and dry matter yields from plots given no supplementary water and protected from rainfall throughout growth than King Edward or Maris Piper. However, on plots kept at or near to field capacity all varieties gave similar yields. Pentland Crown and Majestic were deeper rooting than the other two varieties at the time of tuber formation (when the production of new roots ceased) but the differences in rooting d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

1980
1980
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 7 publications
1
34
0
Order By: Relevance
“…There are differences in potato cultivar susceptibility to drought (Steckel and Gray 1979;Levy 1983Levy , 1986Susnoschi and Shimshi 1985). Screening for drought susceptibility is complicated.…”
Section: Discussionmentioning
confidence: 99%
“…There are differences in potato cultivar susceptibility to drought (Steckel and Gray 1979;Levy 1983Levy , 1986Susnoschi and Shimshi 1985). Screening for drought susceptibility is complicated.…”
Section: Discussionmentioning
confidence: 99%
“…First, it currently assumes that the growth of the potato is not limited by its .water balance. In many cases, however, this assumption is violated (Gandar and Tanner, 1976;Steckel and Gray, 1979;Asfary et al, 1983). Two mechanisms operate here: photosynthesis is closely related to transpiration Allen and Scott, 1980); and water uptake determines the allocation of dry matter to the various parts of the plant (Brouwer, 1962;El Nadi et al, 1969;Davidson, 1969a,b;.…”
Section: Discussionmentioning
confidence: 99%
“…Part of the difficulty in identifying specific factors associated with drought susceptibility is related to the fact that timing and severity of drought is often difficult to impose and maintain under field conditions. Steckel and Gray (1979) examined rooting depth and soil water extraction of potato cultivars differing in drought susceptibility and found that these parameters could not be consistently related to yield responses under varying soil moisture conditions. Stark et al (1991) evaluated the canopy temperatures of 14 potato genotypes under water-stressed and well-watered conditions and found that the most drought tolerant genotypes had the warmest canopy temperatures under well-watered conditions, indicating reduced transpiration rates.…”
Section: Introductionmentioning
confidence: 99%